Extracellular vesicles in the Chronic Myeloid Leukemia scenario: an update about the shuttling of disease markers and therapeutic molecules - Bernardi, Simona; Mulas, Olga; Mutti, Silvia; Costa, Alessandro; Russo, Domenico; La Nasa, Giorgio (Frontiers in Oncology, 2024)
Extracellular vesicles (EVs) are various sets of cell-derived membranous structures containing lipids, nucleic acids, and proteins secreted by both eukaryotic and prokaryotic cells. It is now well recognized that EVs are key intercellular communication mediators, allowing the functional transfer of bioactive chemicals from one cell to another in both healthy and pathological pathways. It is evident that the condition of the producer cells heavily influences the composition of EVs. Hence, phenotypic changes in the parent cells are mirrored in the design of the secreted EVs. As a result, EVs have been investigated for a wide range of medicinal and diagnostic uses in different hematological diseases. EVs have only recently been studied in the context of Chronic Myeloid Leukemia (CML), a blood malignancy defined by the chromosomal rearrangement t(9;22) and the fusion gene BCR-ABL1. The findings range from the impact on pathogenesis to the possible use of EVs as medicinal chemical carriers. This review aims to provide for the first time an update on our understanding of EVs as carriers of CML biomarkers for minimal residual disease monitoring, therapy response, and its management, as well as the limited reports on the use of EVs as therapeutic shuttles for innovative treatment approaches.